Optimizing Islamic Portfolio Formation Using Mathematical and Shariah Approaches - Abdul Aziz; Abdurakhman Abdurakhman (Bank Indonesia, 2026)
This paper introduces the Best Sharia-based Capital Asset Pricing Model (BSCAPM), a mathematical modification of the BCAPM model integrating Islamic finance principles. The study focuses on optimizing the beta in the model, incorporating factors aligned with Islamic principles, such as zakat and purification, while excluding short selling. Using data from the Jakarta Islamic Index (JII) from June 2020 to May 2024, the BSCAPM portfolio outperforms the BCAPM portfolio in terms of the Sharpe ratio. The results suggest that BSCAPM could serve as an effective alternative for modeling in Islamic investments, providing Muslim investors with a Shariah-compliant, optimal portfolio formation model. The research contributes to the underexplored domain of portfolio selection modeling in the Islamic sector, enriching references on asset pricing of Shariah portfolios, particularly in the Indonesian Shariah stock market.